Assessment of Dietary Diversity among Different Ethnic Groups in Karachi - Shahid, Zainab; Wahiba Sheikh Pervaiz; Afnan Sher; Fareeha Shahid; Simra Shahnawaz; Sundus; Mustafa Shabbir; Dua Shabbir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Karachi is known for its rich cultural heritage and ethnic diversity, which includes various communities. This study explores dietary diversity among the diverse ethnic groups of Karachi, addressing cultural influences, socioeconomic factors, and education levels. Aim: To assess the dietary diversity in different ethnic groups of Karachi Methodology: Cross-sectional with survey design was used in the Department of Community Health Science, Bahria University Health Sciences, Karachi from 1st January 2023 to 30th May 2023. Three hundred and ninety-six patients from each of the six ethnic groups were allocated 66 samples (Punjabi, Sindhi, Balochi, Pathan, Saraiki, and Muhajir) in Karachi using a multistage quota. The focus was on individuals aged 20 to 60, excluding those with chronic diseases. In this study, the FFQ standardized questionnaire was used, which was further translated into local languages and then used to collect information. Result: There was a strong association between dietary diversity and ethnicity, with Muhajirs having the most diverse diet, comprising mainly grains and dairy, while Saraiki and Balochi had the least diverse diet. Higher family income correlated with greater dietary diversity. No significant impact of education level, marital status, and age has been determined on dietary diversity. Practical Implication: Dietary diversity is linked to ethnicity and family income, not education or marital status. Interventions to improve nutritional outcomes should be culturally tailored, focusing on diverse diets among ethnic groups and economic stability policies. Education-based strategies may not be as effective, suggesting socioeconomic and cultural factors should be considered. Conclusion: A large urban center study should be planned to investigate cultural casual factors on dietary diversity to determine malnutrition’s root cause and impact. Keywords: Dietary diversity, Ethnicity, Culture, malnutrition, Karachi